DEVELOPMENT OF PALEMBANG LOCAL WISDOM-BASED CIVIC EDUCATION TEACHING SUBJECT IN ELEMENTARY SCHOOL - Amir Hamzah; Tutut Handayani; Nurlaeli Nurlaeli; Ayu Nur Shawmi; Dian Andesta Bujuri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The purpose of this study was to Palembang local wisdom-based develop Civic Education teaching Subject for grade IV in elementary school. This research was research and development. The developed model which was used on this teaching material was ADDIE model which has five stages. They were analysis, design, development, implementation and evaluation. The research subjects were fourth grade students of Islamic Elementary School (MI) Azizan Palembang City. Based on the responses, assessments of design Expert, language Expert, material Expert, and student, the development of these teaching materials has a fairly high level of validity and effectiveness. The results also showed that average learning outcomes on the final test were better at 81.03 compared to the initial test with an average score of 64.71. The significance obtained was 0.000. The significance obtained was less than 0.05. This increase of learning outcome proves that the development of Palembang local wisdom-based teaching materials has an impact on increasing students' understanding of national identity by recognizing and preserving local wisdom.